RENEGOTIATING THE DEPICTION OF DISABILITIES IN AFRICAN DRAMA: FROM ‘BUTIFICATION’ TO ‘NOWIFICATION’ - Shalom ÌBÍRÓNKẸ́; John IWUH (Linguarum Universe, 2025)
This paper introduces the concept of ‘butification’ to critically examine the portrayal of disability in African drama. Building on existing scholarship in disability studies, particularly the works of Tom Shakespeare, Ludmilla Jordanova, and Robert Murphy, it highlights how African dramatic literature perpetuates reductive and dehumanising depictions of disabled individuals. These portrayals often frame disability as an anomaly or burden, focusing on what disabled individuals lack or how their conditions must be overcome for societal healing or order. It analyses key African plays such as Wole Soyinka’s Swamp Dwellers, The Strong Breed and Mad Men and Specialists, Femi Osofisan’s Morountodun and Women of Owu, Ola Rotimi’s The Gods Are Not to Blame and Hopes of the Living Dead, and finds a recurring pattern where disabled characters are portrayed as sacrificial or marginalised “others.” To address this, the paper proposes a shift from ‘butification’ to ‘nowification,’ advocating for representations that highlight the complexity, agency, and autonomy of disabled individuals. ‘Nowification’ reimagines disabled characters not as burdens, but as integral parts of human diversity, possessing dynamic identities and contributing to societal narratives. This theoretical shift aims to bridge the gap in African literary and theatrical traditions by promoting more ethical and inclusive portrayals that reflect the lived realities of people with disabilities. Through this lens, the paper advocates for a paradigm shift in African drama, promoting nuanced and empowering depictions that can reshape cultural understandings of disability and enrich the broader discourse on disability representation.